Identifikasi Konsep Fisika pada Bidang Miring Berbantuan Aplikasi Algodoo - Aufa Maulida Fitrianingrum; Ishak Pawarangan (Jurnal FisTa : Fisika dan Terapannya, 2024)
This study aimed to determine the effectiveness of using the Algodoo application in the process of understanding the motion of objects descending an inclined plane. The method used in this research was an experimental method with a quantitative approach to identify the physical quantities of objects descending an inclined plane. The physical quantities were acceleration, velocity, force, potential energy, kinetic energy, and mechanical energy. Based on the data analysis, the acceleration of the object was found to be 4.9 m/s². The velocity of the object changed in a linear equation of 4.9t m/s. The potential energy decreased as the object descends the inclined plane. The kinetic energy of the object increased with the equation 1.2005t² J. The total of potential energy and kinetic energy, the mechanical energy, remained constant at 2.6956 J. These results indicated that Algodoo can be used to analyze physical quantities whose experimental values are close to theoretical ones. Therefore, Algodoo has the potential as an effective learning resource for understanding physics concepts.